Socioscientific Issues (SSI) Strategy Adjacent to Ethnoscience: A Critical Analysis of Science Reconstruction - Moh. Irma Sukarelawan; Mohd Fauzi Sedon; Che Nidzam Che Ahmad; Sukarmin Sukarmin; Misbah Misbah; Ahmad Khoiri; Qori Agussuryani (Postgraduate, University of Mataram, 2022)
Low students' reconstruction skills in understanding science through local issues in society. The purpose of the study was to analyze the categorization of science reconstruction skills and test the effectiveness of the ethnoscience-adjacent Socioscientific Issues (SSI) strategy. Type of quasi-experimental quantitative research with independent sample type t-statistical design. Purposive sampling technique with a total of 65 high school students from 3 different schools clustered, namely schools in the village category, intermediate category, and city category. School categories are based on mileage from the city center. The data collection tool uses student science reconstruction tests and SSI strategy implementation questionnaires. The effectiveness of the SSI strategy consists of pretest and post-test data of students' science reconstruction skills. Data analysis techniques use the t-test and Manova test. The results showed that the categorization of students' science reconstruction skills was dominant in the Other Smart Kids (OSK) category by a p-value of 0.026 < 0.05; Students felt unfamiliar with the culture being studied, even though students' knowledge of science increased. The MANOVA test obtained the results of the experimental class (known with KE) = 0.674 and the Fcount KE = 17.974, showing that the SSI strategy with ethnoscience proximity was very effective in empowering student's science reconstruction skills simultaneously (SMA A, B, and C) with significant influence. Research recommendations that science reconstruction skills give the meaning of learning about how to appreciate and preserve the traditions and culture of society as a formation of the nation's character.